Window impression technique for a single denture with maxillary anterior flabby ridge - Ikbal, Muhammad; Dammar, Irfan; Mude, Acing H.; MIR, Andi A. (Journal of Case Reports in Dental Medicine, 2019)
Objective:Theaims to explain the window impression technique for a single denture with flabby tissue area in maxillary anterior ridge in the form of case report.Methods:The clinical examination showed the maxillary complete edentulousridgewithflabbyridgeareainthemaxillaryanteriorregion opposing the anterior natural teeth in the mandibular.Results: There were various impression techniques used in the management of flabby tissue in the maxillary anterior ridge for a single denture cases.Conclusion: The window impression technique is one of the proper techniques used in the management of flabby tissue for the single denture impression.Keyword: Anterior ridge, Flabby ridge, Single denture